(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2020)
Chronic Kidney Disease (CKD) is a global health threat with socioeconomic and public health consequences. Estimates on the Global Burden of Disease (GBD) indicated that kidney diseases were responsible for 2,993,000 years of life lost (YLL) and 38,104,000 disability-adjusted life years (DALYs) lost globally. The increasing incidence and prevalence of end-stage renal disease (ESRD) seem inevitable. An influx of dialysis patients had increased to dialysis centers, especially in the private sector. This study was conceptualized to help ESRD-clients undergoing dialysis address the health needs and other concerns of these clients. The study utilized the quantitative method, a descriptive survey with a developmental approach. The participants of the study, purposively chosen, included 20 nurses, 180 patients undergoing hemodialysis, and 194 significant others such as watchers or relatives in selected dialysis clinics in La Union during the period of June-December 2019. The result showed an impressive health status of the respondents and a moderate level of adherence to their regimen of care. Consequently, the physical, social, economic, emotional, and spiritual factors highly affect the health status of ESRD-diagnosed clients. Furthermore, the nurses, ESRD patients, and their significant others did not vary significantly on their assessment of the health status and adherence to the regimen of care of the clients, and on the effect of the factors to the clients’ health status and adherence to the regimen of ESRD patients. Lastly, no significant relationship was established on the interplay between and among the variables. The findings of the study serve as a basis for healthcare providers in advocating for ESRD patients to complete their sessions and strictly adhere to their regimen of care. Continuous interventions to improve treatment adherence, such as health education and counseling, are likewise recommended strongly.